188 INTRAPULMONARY ADMINISTRATION OF MESENCHYMAL STEM CELLS REDUCES ENDOTOXIN-INDUCED ACUTE LUNG INJURY AND MORTALITY IN A MOUSE MODEL. (1st January 2006) - Gupta, N.; Su, X.; Serikov, V.; Matthay, M.
Abstract : Purpose: Mesenchymal stem cells are bone marrow-derived cells that have the ability to differentiate into cells of different lineages including pulmonary epithelium. Prior studies in lung injury models have focused on administration of stem cells by the intravenous route. Our objective was to test the potential benefit from intrapulmonary administration of mesenchymal stem cells in a mouse model of endotoxin-induced acute lung injury by measuring extravascular lung water and survival. Methods: The mesenchymal stem cells were obtained from GFP-C57BL/6 mice and were propagated in culture. C57BL/6 mice were used for all experiments, and acute lung injury was established by intratracheal (it) instillation of LPS from E. coli 055:B5 (5 mg/kg). Four hours after LPS instillation, mice received by its instillation either mesenchymal stem cells (750, 000 cells in 30 μL) or PBS (30 μL). Mice were followed for 48 hours. The lungs were harvested and blood samples collected at 48 hours or earlier if the mice died. Further experiments using the same protocol were done with bronchoalveolar lavage (BAL) and plasma samples for the measurement of TNF-α and MIP-2 by R&D ELISA kits. Results: Intrapulmonary mesenchymal stem cells reduced pulmonary edema compared to controls treated with PBS (wet-to-dry lung water 5.4 ± 1.3 vs 6.9 ± 1.2 g water/g dry lung, data as mean ± SD, p < .01, n = 12 for both groups). In addition, the stem cells improved survival over the 48-hour time period (100% in the stem cell group vs 31% in the control group, p < .01, n = 13 for both groups). Furthermore, mesenchymal stem cells decreased both the BAL levels of TNF-α and MIP-2 compared to control mice (BAL TNF-α: 174 ± 92 vs 798 ± 531 pg/mL, p = .02; BAL MIP-2: 207 ± 67 vs 717 ± 567 pg/mL, p = .05; all comparisons are stem cell treated vs control group, n = 6 for both groups). Significant reductions were also found in the plasma levels of TNF-α and MIP-2 in the stem cell versus PBS control mice. Conclusions: In LPS-induced acute lung injury in mice, the intrapulmonary administration of mesenchymal stem cells reduces the severity of lung injury and improves survival when given 4 hours after LPS instillation into the lung. This benefit appears to be mediated in part through a down-regulation of the acute inflammatory responses to endotoxin.